Characterization and application of newly isolated nisin producing Lactococcus lactis strains for control of Listeria monocytogenes growth in fresh cheese. (January 2018) - Kondrotiene, Kristina; Kasnauskyte, Neringa; Serniene, Loreta; Gölz, Greta; Alter, Thomas; Kaskoniene, Vilma; Maruska, Audrius Sigitas; Malakauskas, Mindaugas
Abstract: This study was aimed to screen for nisin producing Lactococcus lactis strains with prominent antimicrobial and technological characteristics applicable for the dairy industry. Twelve out of 181 Lactococcus spp. strains isolated from goat and cow milk, fermented wheat and buckwheat samples were identified as L. lactis strains harbouring nisin A, Z or novel nisin variant GLc03 genes. For the first time technological characteristics of L. lactis strains harbouring nisin variant GLc03 were evaluated. All 12 isolated strains showed clear antagonistic activity against tested food spoilage and pathogenic bacteria. Moreover, strains encoding nisin Z presented favorable enzymatic activities of acid phosphatase, esterase lipase and phosphohydrolase. However, strains encoding novel nisin variant GLc03 were lacking appropriate technological characteristics being resistant to tetracycline and producing harmful β-glucosidase, therefore these strains are not applicable for the dairy food production. Two nisin A producing L. lactis strains were poor acidifiers and one strain showed resistance to tetracycline. Three strains were selected according to safety and technological criteria and were examined in fresh cheese production for control of Listeria monocytogenes growth. Listeria numbers were significantly reduced (P < 0.001) in model cheese suggesting the application of these strains for fresh cheese safety improvement. Highlights: 12 Lactococcus lactis strains were producers of bacteriocin nisin A, Z or novel variant GLc03. Evaluation of technological properties of L. lactis strains with novel nisin variant GLc03. Selected nis + L. lactis strains significantly reduced listeria numbers in fresh cheese.